Research on the Construction of a Digital Resource Repository for Marine English for Shipbuilding and Repair Based on Blended Learning - Hu, Xiaoli; Hu, Honghua (Journal of Educational Research and Policies, 2025)
This paper conducts an in-depth study on the construction of a digital resource repository for Marine English for Shipbuilding and Repair (hereinafter referred to as MESR) against the backdrop of blended learning. Firstly, starting from the characteristics and advantages of blended learning, it outlines the concept and role of a digital resource repository for MESR. Subsequently, through the analysis of teaching needs and learner demands, the requirements for constructing such a resource repository are clarified. On this basis, strategies for constructing a digital resource repository for MESR based on blended learning are proposed, including content development strategies and technical support strategies. Specifically, content development strategies encompass the integration of materials such as textbooks, teaching cases, and instructional videos; technical support strategies propose corresponding technical solutions for the resource repository’s construction from the perspectives of network technology, database technology, and virtual reality technology. Finally, the research findings are summarized, and future development directions for the MESR digital resource repository are suggested. This research holds significant theoretical and practical value for enhancing the effectiveness of MESR teaching and promoting the application of digital educational resources.